Altered ethanolamine plasmalogen and phosphatidylethanolamine levels in blood plasma of patients with bipolar disorder. Issue 3 (3rd February 2020) - Ogawa, Shintaro; Hattori, Kotaro; Ota, Miho; Hidese, Shinsuke; Miyakawa, Tomoko; Matsumura, Ryo; Yokota, Yuuki; Ishida, Ikki; Matsuo, Junko; Yoshida, Sumiko; Yamazaki, Yasuyo; Goodenowe, Dayan; et al.
Abstract : Aim: Ethanolamine‐containing phospholipids are synthesized in endoplasmic reticulum (ER) and mitochondria. ER stress and mitochondrial dysfunction have been implicated in bipolar disorder (BP). In this study, we aimed to examine the relationship of ethanolamine plasmalogen (PLE) and phosphatidylethanolamine (PTE) levels in blood plasma with BP. Methods: Plasma PLE and PTE levels were compared between 34 patients with BP (DSM‐IV) and 38 healthy control participants matched for age, sex, and ethnicity (Japanese). Furthermore, the relationships of plasma PLE and PTE levels with clinical variables were explored. Results: Plasma PLE levels were significantly lower in patients with BP than in healthy controls ( P = 0.0033). In subgroup analyses, plasma PLE levels were significantly lower in patients with BP type I (BP I) than in healthy controls ( P = 0.0047); furthermore, plasma PTE levels were significantly lower in patients with BP I than in controls ( P = 0.016) and patients with BP type II (BP II) ( P = 0.010). Receiver‐operating characteristic curve analysis revealed that the discriminatory power of plasma PTE levels for distinguishing between BP I and II was fair (area under the curve = 0.78; P = 0.0095). There were no significant correlations of plasma PLE or PTE levels with depression or manic symptoms in patients. Conclusions: Plasma PLE and PTE levels were associated with BP I, but not with BP II. Moreover, plasma PTE levels differed between patients with BP I and II. Our findings highlight the importance of ethanolamine phospholipids in the pathophysiology of BP, especially BP I.